Implementation of Concurrency Control to Prevent Race Condition in a Web-Based Billiard Table Reservation System (Journal of Innovation and Technology Polbeng Series on Informatics (INOVTEK Polbeng - Seri Informatika), 2025)
The development of information technology has driven the digitalization of various services, including web-based billiard table reservation systems. However, web systems that operate in real time are prone to race conditions when multiple users attempt to book the same table simultaneously, potentially leading to double booking. This study aims to implement a Concurrency Control mechanism using the Firebase Transaction feature to prevent such booking conflicts. The research method adopts a Research and Development (R&D) approach with the ADDIE model, which consists of the stages of Analysis, Design, Development, Implementation, and Evaluation. Furthermore, testing was conducted through pre-test and post-test simulations across 10 trials with concurrent users ranging from 2 to 11 individuals. In the pre-test stage, all users were able to successfully book the same resource simultaneously, resulting in 100% double booking across all trials. In the post-test stage, after implementing the Concurrency Control mechanism using Firebase Transaction, only one request was accepted out of the same 10 trials, while all other requests were automatically rejected, resulting in 0% double booking. These findings demonstrate that the applied concurrency control mechanism is effective in maintaining data consistency and preventing race conditions in the web-based billiard table reservation system.